A comprehensive design method for segmented thermoelectric generator. (December 2015) - Zhang, Guobin; Fan, Linhao; Niu, Zhiqiang; Jiao, Kui; Diao, Hai; Du, Qing; Shu, Gequn
Highlights: A new method for design of segmented TEG is proposed. Optimal length ratios for output power and efficiency are different. Material properties, geometry and heat transfer all need to be considered. This method is approved to be accurate and time-efficient. Abstract: A comprehensive method for indicating the length ratio of segmented thermoelectric generator (TEG) is proposed to increase the output power and thermoelectric conversion efficiency. It is found that for a segmented TEG, there is an optimal length ratio corresponding to the highest maximum output power or thermoelectric conversion efficiency, which is not only dependent on the material properties but also the heat transfer conditions and geometry structure. The optimal length ratios corresponding to the output power and thermoelectric conversion efficiency are different. This method is also validated, and the error is within a reasonable range, indicating that this method can be used accurately and time-efficiently for the design of segmented TEGs.